Beneficiilie exerciţiilor fizice pentru studenţii cu dereglări de sănătate ale sistemului nervos [Articol] - Morari, Alexandru (USARB, 2016)
Physical exercise positively influences nervous activity, stimulating the transmission speed of nervous influxes with special effects in increasing mental efficiency and concentration capacity. The exercise positively affects tired or sick nervous centers, which are required in excess, restoring them. This article aims to train students a healthy concept about movement, about its positive effects obtained through systematic practice of physical exercise, to instill interest and desire to move. The article suggests a range of affordable and effective exercises for students with different disorders of the nervous system.
Keywords: physical exercise; nervous activity; transmission speed of nervous influxes; students with different disorders of the nervous system; exerciţiu fizic; activitatea nervoasă; viteza de transmitere a influxurilor nervoase; studenţi cu diferite tulburări ale sistemului nervos